Risk factors and outcomes in patients undergoing minimally invasive hepatectomy with unplanned conversion: a contemporary NSQIP analysis. Issue 5 (May 2023) - Vining, Charles C.; Al Abbas, Amr I.; Kuchta, Kristine; Paterakos, Pierce; Choi, Sung H.; Talamonti, Mark; Hogg, Melissa E.
Abstract: Background: Minimally invasive techniques are growing for hepatectomies. Laparoscopic and robotic liver resections have been shown to differ in conversions. We hypothesize that robotic approach will have decreased conversion to open and complications despite being a newer technique than laparoscopy. Methods: ACS NSQIP study using the targeted Liver PUF from 2014 to 2020. Patients grouped based on hepatectomy type and approach. Multivariable and propensity scored matching (PSM) was used to analyze the groups. Results: Of 7767 patients who underwent hepatectomy, 6834 were laparoscopic and 933 were robotic. The rate of conversions was significantly lower in robotic vs laparoscopic (7.8% vs 14.7%; p < 0.001). Robotic hepatectomy was associated with decreased conversion for minor (6.2% vs 13.1%; p < 0.001), but not major, right, or left hepatectomy. Operative factors associated with conversion included Pringle (OR = 2.09 [95% CI 1.05–4.19]; p = 0.0369), and a laparoscopic approach (OR = 1.96 [95% CI 1.53–2.52]; p < 0.001). Undergoing conversion was associated with increases in bile leak (13.7% vs 4.9%; p < 0.001), readmission (11.5% vs 6.1%; p < 0.001), mortality (2.1% vs 0.6%; p < 0.001), length of stay (5 days vs 3 days; p < 0.001), and surgical (30.5% vs 10.1%; p < 0.001), wound (4.9% vs 1.5%; p < 0.001) and medical (17.5% vs 6.7%; p < 0.001) complications. Conclusion: Minimally invasive hepatectomy with conversion is associated with increased complications, and conversion is increased in the laparoscopic compared to a robotic approach.